TECHNICAL-SCIENTIFIC VISIT AT SOPHIA UNIVERSITY INSTITUTE: SOME REFLECTIONS ON LOVE TO THE WORLD - Auer, Franceila; Franco de Mello Aquino Pinheiro, Larissa; Carvalho de Araújo, Vania (Revista Ciranda, 2022)
This paper aims to discuss a technical-scientific visit held at the Sophia University Institute, in Figline and Incisa-Valdarno, in the region of Tuscany - Italy, in articulation with the thoughts of Hannah Arendt and the experience of Chiara Lubich. To do so, it adopts an experience report written in an essay format and mobilizes the concept of love in both authors. The outcomes indicate that the educational proposal idealized by Chiara Lubich surpasses the concern with the academic training of the students only, because they reach a common experience of the world and responsibility for the community, whose knowledge produced and study projects go beyond the university scenario and are associated with local demands. These experiences seem to align with the Arendtian reflections on amor mundi as a human device to connect to the other in action, speech and inter-relationships woven in social life as well as in the commitment to others aiming to build a more humanized society.